2021
DOI: 10.1101/2021.05.25.21257434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographical and temporal distribution of SARS-CoV-2 globally: An attempt to correlate case fatality rate with the circulating dominant SARS-CoV-2 clades

Abstract: Uncontrolled high transmission is driving the continuous evolution of SARS-CoV-2, leading to the nonstop emergence of the new variants with varying sensitivity to the neutralizing antibodies and vaccines. We have analysed of 8,82,740 SARS-CoV-2 genome sequences, collected and sequenced during late December 2019 to 25 March 2021 from all across the world. The findings revealed differences in temporal and spatial distribution, and predominance of various clades/variants among six different continents.We found no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…B.1.1.7, B.1.351, P.1 and B.1.617.2 are variants with higher transmissibility and are designated as ‘Variants of Concern’ by the WHO ( https://www.who.int/en/activities/tracking-SARS-CoV-2-variants/ ). B.1.525 belongs to the ‘Variants of Interest’ category Several candidate mAbs, F461G11, F461G15, and F461G16 demonstrated comparable or increased neutralizing activities to all the variants and the reference strain (hCoV-19/Canada/ON_ON-VIDO-01-2/2020, EPI_ISL_425177, which was isolated at the early stage of this pandemic and belong to the same L clade as the GISAD designated official reference strain WIV04) ( Sarkar et al, 2021 ) indicating that these mAbs have broad-spectrum antiviral potency. Moreover, the three candidate mAbs showed a four-to eight-fold increase of neutralization of B.1.617.2, the variant with over 50% higher transmissibility than B.1.1.7 ( Public Health England, 2021b ), and increased resistance to tested vaccines ( Wall et al, 2021 ; Bernal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…B.1.1.7, B.1.351, P.1 and B.1.617.2 are variants with higher transmissibility and are designated as ‘Variants of Concern’ by the WHO ( https://www.who.int/en/activities/tracking-SARS-CoV-2-variants/ ). B.1.525 belongs to the ‘Variants of Interest’ category Several candidate mAbs, F461G11, F461G15, and F461G16 demonstrated comparable or increased neutralizing activities to all the variants and the reference strain (hCoV-19/Canada/ON_ON-VIDO-01-2/2020, EPI_ISL_425177, which was isolated at the early stage of this pandemic and belong to the same L clade as the GISAD designated official reference strain WIV04) ( Sarkar et al, 2021 ) indicating that these mAbs have broad-spectrum antiviral potency. Moreover, the three candidate mAbs showed a four-to eight-fold increase of neutralization of B.1.617.2, the variant with over 50% higher transmissibility than B.1.1.7 ( Public Health England, 2021b ), and increased resistance to tested vaccines ( Wall et al, 2021 ; Bernal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, another analysis of country-based case fatality rates (CFR) found no relationship between mortality and clade, at least through March 2021. [75] To the extent that patient status in GISAID metadata does show variation, other studies using logistic regression and conventional statistical techniques found it to largely reflect worse outcomes for older males, consistent with commonly understood clinical experience, while it was difficult to discern variation at the clade or sequence levels. [76], [77] Other more complex analysis has included the use of deep neural networks, in particular, a combination of convolutional neural network (CNN) and recurrent neural network (RNN), which attempted to predict what mutations would increase virulence severity based on countrywide death statistics.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…The GISAID dataset and focused patient studies (which are often the source of the data available on GISAID) have enabled researchers to study the potential link between sequence variation and virulence. These studies have included analysis of single nucleotide polymorphisms (SNP) and genome wide association studies [70], [71], literature meta-analysis [72], genome wide association studies [73], and the incidence and prevalence of mutations in GISAID entries with clinical metadata [74], [75]. The results of these studies found some correlation of symptomatic or severe disease with spike variants such as D614G, however, none of these have been verified elsewhere.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%